Robust Adaptive Fault-Tolerant Coordinated Control for Biaxial Gantry System with Friction Compensation - Wang, Kangjun; Liu, Xiangbin; Su, Hongye (2020 16th International Conference on Control, Automation, Robotics and Vision (ICARCV), 2020)
In this paper, a novel robust adaptive fault-tolerant coordinated control is proposed for the contour tracking problem of unknown biaxial linear-motor-driven gantry system subject to time-varying actuator faults. Firstly, the dynamic model of the contour error is established by coordinate transformation. The time-varying actuator faults including loss of effectiveness and bias faults with unknown failure time are considered in controller design. The robust adaption law with smooth projection modification is developed to handle for the effect of parametric uncertainties on the system. The proposed control scheme can guarantee that all the signals in the closed-loop system are ultimately bounded even if time-varying actuator faults of the gantry system occur. Finally, two numerical simulations are conducted to show the effectiveness of the proposed control method.